2014
DOI: 10.1002/14651858.cd010254.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin for lowering lipids

Abstract: Background Rosuvastatin is one of the most potent statins and is currently widely prescribed. It is therefore important to know the dose-related magnitude of effect of rosuvastatin on blood lipids. Objectives Primary objective To quantify the effects of various doses of rosuvastatin on serum total cholesterol, low-density lipoprotein (LDL)-cholesterol, highdensity lipoprotein (HDL)-cholesterol, non-HDL-cholesterol and triglycerides in participants with and without evidence of cardiovascular disease. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 208 publications
0
10
0
Order By: Relevance
“…This difference can be due to the relatively low baseline TG levels in our study compared to those usually reported in trials. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This difference can be due to the relatively low baseline TG levels in our study compared to those usually reported in trials. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The critical role played by LDL-C in atherosclerosis has prompted the development of rational strategies to counter the pathogenic effects of hypercholesterolemia. The use of statins (inhibitors of HMG-CoA reductase, the rate-controlling enzyme of the mevalonate, and cholesterol synthesis pathways) as a pharmacological approach to lower cholesterol levels is one of the most widely used therapies in the treatment of atherosclerosis and acute coronary syndromes, as these drugs show consistent clinical event reductions with a very good safety profile (Adams et al, 2014). Other clinical studies reveal that the use of ezetimibe (an inhibitor of intestinal cholesterol absorption) considerably reduces LDL-C blood levels when combined with statins (Catapano et al, 2016).…”
Section: Importance Of Cardiopulmonary Diseasesmentioning
confidence: 99%
“…Other clinical studies reveal that the use of ezetimibe (an inhibitor of intestinal cholesterol absorption) considerably reduces LDL-C blood levels when combined with statins (Catapano et al, 2016). An alternative approach is the administration of fibrates, a particular class of agonists of the peroxisome proliferator-activated receptor α (PPAR-α) a regulator of lipoprotein metabolism, showing a good effect in lowering TG levels as mono-therapy, even though the results are not as promising as for the statins (Adams et al, 2014). Recently, a large multi-scale and multiethnic study was undertaken to better understand the role of genetic and environmental factors in CVD and to identify genetic variants associated to blood lipids levels (Klarin et al, 2018).…”
Section: Importance Of Cardiopulmonary Diseasesmentioning
confidence: 99%
“…Rosuvastatin is the most powerful widely‐prescribed statin worldwide; due to its rapid absorption, achieving peak plasma concentration within three hours. Moreover, its lipid‐lowering effect is not influenced by the time‐of‐day by which it is administered; due to the comparatively long half‐life of 20 hours [ 16 , 17 ]. Accordingly, the current study has been initiated to investigate, on mechanism-based, the possible therapeutic effects of rosuvastatin when combined with androgen deprivation in metastatic prostate cancer patients.…”
Section: Introductionmentioning
confidence: 99%